The ark of nuh: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This tale recounts the story of Prophet Noah and his ark, symbolizing salvation amidst a great flood. It underscores themes of obedience, faith, and the promise of renewal.